2019
DOI: 10.1371/journal.pone.0216809
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic ring injury in the elderly: Fragile patients with substantial mortality rates and long-term physical impairment

Abstract: Background Pelvic ring injuries in the elderly often occur after low-energy accidents. They may result in prolonged immobilization, complications and an intense rehabilitation process. The aim of this study was to assess mortality, physical functioning and quality of life (QoL) in elderly patients with pelvic ring injuries. Methods A cross-sectional study was performed including all elderly patients (� 65 years) admitted for a pelvic ring injury between 2007-2016. Mortality and survival were evaluated and pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 24 publications
2
25
3
1
Order By: Relevance
“…In the studies listed in Table 4 , there always is an excess mortality in FFP patients when compared with the general population of the same age, be it in Scotland, the Netherlands, Austria, or Germany. As in the publications of Krappinger [ 8 ] and Banierink [ 20 ], we found a strong dependence of the one-year mortality on age: the rates of our patients below and above the age of 80 were 8.8% resp. 22.2%.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In the studies listed in Table 4 , there always is an excess mortality in FFP patients when compared with the general population of the same age, be it in Scotland, the Netherlands, Austria, or Germany. As in the publications of Krappinger [ 8 ] and Banierink [ 20 ], we found a strong dependence of the one-year mortality on age: the rates of our patients below and above the age of 80 were 8.8% resp. 22.2%.…”
Section: Discussionsupporting
confidence: 87%
“…We did not find a remarkable difference in the one-year mortality between our study population without involvement of the posterior pelvic ring and other study populations, in which at least a part had involvement in the posterior pelvic ring. The one-year mortality rate of 16.7% in our patient cohort is situated at the lower end of data given in the published series in Table 4 , ranging from 11.2% [ 8 ] to 26.8% [ 20 ].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Mortality within the 1st year after pelvic fracture has with few exceptions been investigated among inpatients only. A Dutch study of pelvic fractures among inpatients ≥ 65 years found a 1-year mortality of 27% (Banierink et al 2019), substantially higher than the 21% found in our study. A German study from 2017, including both in-and outpatients, found a 1-year mortality of 21% (Andrich et al 2017), like our results.…”
Section: Mortalitycontrasting
confidence: 85%
“…Pelvic insufficiency fractures (PIFs) are recognized as one of the late morbidities following RT for pelvic region [5]. Pelvic injury causes a significant decrease in the patients' quality of life (QOL) [6], Thus, we should consider the significance of PIFs as non-negligible late RT morbidities.…”
Section: Introductionmentioning
confidence: 99%